2017
DOI: 10.1007/s12603-016-0754-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal residue and aspiration and the relationship with clinical/nutritional status of patients with oropharyngeal dysphagia submitted to videofluoroscopy

Abstract: In the present study, neurologic diseases, HNC, male sex and underweight were associated to impaired swallowing efficacy. Underweight, independently of the other variables, was not associated with impaired swallowing safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
1
12
0
2
Order By: Relevance
“…Still, this finding highlights an imbalance in research focus that has the potential to minimize the occurrence and clinical importance of post-swallow residue. In non-MND populations, post-swallow residue has been linked with malnutrition [8082], which poses an inevitable concern faced by individuals with ALS and related MNDs. Further, some reports from instrumental assessment show that the occurrence of post-swallow residue is more frequent than aspiration [44,52,5860,62] in patients with ALS, and may even present an independent risk factor for later aspiration events [39,40,66].…”
Section: Discussionmentioning
confidence: 99%
“…Still, this finding highlights an imbalance in research focus that has the potential to minimize the occurrence and clinical importance of post-swallow residue. In non-MND populations, post-swallow residue has been linked with malnutrition [8082], which poses an inevitable concern faced by individuals with ALS and related MNDs. Further, some reports from instrumental assessment show that the occurrence of post-swallow residue is more frequent than aspiration [44,52,5860,62] in patients with ALS, and may even present an independent risk factor for later aspiration events [39,40,66].…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia severity, swallowing safety, and swallowing efficacy were rated with validated ordinal scales. Swallowing safety refers to the ability to transfer the bolus from the mouth to the stomach without penetration or aspiration into the lower airways, which is associated with respiratory complications; swallowing efficacy refers to the ability to transfer the bolus from the mouth to the stomach without post-swallow pharyngeal residue and is associated with nutritional complications 28 , 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients who aspirate food and liquids into the airway are at increased risk of developing pneumonia 8 . Factors associated with increased aspiration risk include salivary pooling 9 , impaired sensation 10 , reduced airway protection 11 and pharyngeal residue 12,13 . Murray et al reported a significant association between accumulated secretions and aspiration of food and/or drink, observed during endoscopic evaluation of older individuals, including patients with mixed aetiology and healthy persons 9 .…”
Section: Introductionmentioning
confidence: 99%